Pengembangan Media Komik (Sahabat Dari Langit) Untuk Mencegah Perilaku Bullying Siswa Kelas 4 Di SDN Bapangan - Salamatus Sa'diyah, Nadia; Rofiqoh, Naili (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study aims to develop an educational comic titled Sahabat dari Langit (Friend from the Sky) as an instructional medium to prevent bullying among fourth-grade students at SDN Bapangan. The research follows the Research and Development (R&D) method using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The analysis phase revealed the absence of a specific medium that effectively conveys anti-bullying values, while some students had not yet fully understood the forms and impacts of bullying. The comic was developed using a visual approach and age-appropriate contextual storytelling, promoting values such as empathy, tolerance, and conflict resolution. Expert validation results placed the media in the “Highly Appropriate” category in terms of content and visual design. Trial implementation showed a significant improvement in students’ understanding, as seen from the comparison of pre-test and post-test scores, along with positive responses from both teachers and students. With its engaging narrative and communicative visuals, Sahabat dari Langit is considered a feasible and innovative alternative for character education and bullying prevention in elementary schools.